The Effect of Board Governance on Business Zakat Compliance with Trust and Transparency as Intervening Variable - Muslichah, Muslichah; Bashir, Mohamed Sharif; Arniati, Tutik (UIN Sunan Kudus, 2024)
Zakat is a mandatory contribution of a specific portion of one's assets that every Muslim must make after they meet the stated criteria. Zakat is disbursed to the designated beneficiaries (asnaf) who are eligible to receive it. This study aims to examine the effect of board governance on business zakat compliance with public trust and transparency as intervening variable. This study will be carried out in East Java, Indonesia. The respondents of this study business zakat payers in East Java who pay zakat through Lazismu. Data will be gathered using the survey methodology. Partial least squire structural equation (PLS-SEM) path modelling will be employed to analyze the data. The study's findings suggest a direct relationship between board governance and zakat compliance. The results of this study further demonstrate that the relationship between board governance and zakat compliance is mediated by trust and transparency.